Identifying baseline immune-related biomarkers to predict clinical outcome of immunotherapy. Issue 1 (16th May 2017) - Gnjatic, Sacha; Bronte, Vincenzo; Brunet, Laura Rosa; Butler, Marcus O.; Disis, Mary L.; Galon, Jérôme; Hakansson, Leif G.; Hanks, Brent A.; Karanikas, Vaios; Khleif, Samir N.; Kirkwood, John M.; Miller, Lance D.; et al.
Abstract : As cancer strikes, individuals vary not only in terms of factors that contribute to its occurrence and development, but as importantly, in their capacity to respond to treatment. While exciting new therapeutic options that mobilize the immune system against cancer have led to breakthroughs for a variety of malignancies, success is limited to a subset of patients. Pre-existing immunological features of both the host and the tumor may contribute to how patients will eventually fare with immunotherapy. A broad understanding of baseline immunity, both in the periphery and in the tumor microenvironment, is needed in order to fully realize the potential of cancer immunotherapy. Such interrogation of the tumor, blood, and host immune parameters prior to treatment is expected to identify biomarkers predictive of clinical outcome as well as to elucidate why some patients fail to respond to immunotherapy. To approach these opportunities for progress, the Society for Immunotherapy of Cancer (SITC) reconvened the Immune Biomarkers Task Force. Comprised of an international multidisciplinary panel of experts, Working Group 4 sought to make recommendations that focus on the complexity of the tumor microenvironment, with its diversity of immune genes, proteins, cells, and pathways naturally present at baseline and in circulation, and novel tools to aid in such broad analyses.